Large-size-mismatch co-dopants for colossal permittivity rutile TiO2 ceramics with temperature stability. Issue 4 (April 2018) - Yu, Yang; Li, Wei-Li; Zhao, Yu; Zhang, Tian-Dong; Song, Rui-Xuan; Zhang, Yu-Lei; Wang, Zhen-Yu; Fei, Wei-Dong
Abstract: Colossal permittivity (CP) in donor-accepter co-doped rutile TiO2 has attracted significant interest. Here, the CP behavior of (Ta + La) co-doped rutile TiO2 ceramics were studied, where the ionic radii of Ta 5+ and La 3+ are much larger than that of Ti 4+ . The ceramics with an extremely low doping exhibit colossal dielectric permittivity (∼2.6 × 10 4 ) with an acceptable low dielectric loss (<0.07) in the frequency range from 40 to 10 6 Hz. The CP properties obtained in (Ta + La) co-doped TiO2 ceramics show excellent temperature stability over a wide temperature range of 20–400 °C. The X-ray diffraction analysis and the density functional theory calculation illustrates that the La2 3+ V o Ti2 3+ and Ta2 5+ Ti 3+ Ti 4+ defect complexes with the lowest energy are responsible for the enhanced dielectric properties. Moreover, the defect complex formed by large-size trivalent substitutions and oxygen vacancy is very stable, and assists in improving temperature stability of the dielectric properties of co-doped rutile TiO2 ceramics.